Quality performance of Universiti Teknologi Mara Sarawak 2006 / Iris Syawe Seh Ling ...[et al.] - Syawe, Seh Ling; Hamali, Jamil; Lee, Beng Yong; Sarkawi, Adib (Universiti Teknologi Mara Cawangan Sarawak, 2008)
This project is an effort for continuous monitoring on quality performance of Universiti Teknologi MARA (UiTM) Sarawak based on the recommendations of the 2004 study. The project measured the quality index on the standard of services rendered to staff and students in the form of QMeasure Index on customer satisfaction. The first part of the project was undertaken by conducting questionnaire surveys on students and staff. The questionnaires for students and staff used in 2004 study were updated to overcome the limitations of that study. A total of 1,765 students and 449 staff responded. In the second part of the project, the QMeasure Instrument III for self-evaluation based on the eight criteria laid out in the QMeasure were refined and up-dated to incorporate as much as possible the items in the Malcom Baldrige "2003 Education Criteria For Performance Excellence" model. Scoring system of this model was utilised to assign scores. The QMeasure Index™ was derived by using statistical methods. Results showed that UiTM Sarawak has achieved a QMeasure Index of 5.9 out of 7.0. This is an improvement from the index of 5.6 obtained in 2002 study. Although the index indicates that UiTM Sarawak is progressing well on its quality journey, there is still plenty of room for further improvements based on the feedback from the students and staff.